Research on efficient cross trust-domain group authentication with conditional privacy of vehicle platoon under blockchian architecture - Yingjie XIA; Siyu ZHU; Xuejiao LIU (Tongxin xuebao)
In order to balance the security and efficiency of vehicle platoon cross trust-domain identity authentication, an efficient cross trust-domain group authentication scheme with conditional privacy of vehicle platoon under blockchian architecture was proposed.A novel block structure BM-Tree was designed for vehicle platoon identity authentication, which provided support for efficient cross trust-domain group authentication by sharing the group authentication parame-ters on the blockchain.Dynamic pseudonym was used for vehicle identity privacy-preserving and bilinear mapping was used to transform the trust-domain parameters, which realized cross trust-domain group authentication with conditional privacy.An efficient group authentication protocol based on BM-Tree was proposed, which realized batch identity au-thentication and re-authentication of vehicle platoon.The proposed scheme has better performance than existing cross trust-domain authentication methods in terms of security and computational overhead.Experimental result shows that the authentication delay is reduced by 29%, 25% and 53% on average, respectively compared with BLA, MDPA and BBA.